Glutathionyl Hemoglobin and Its Emerging Role as a Clinical Biomarker of Chronic Oxidative Stress - Andrea Scirè; Giulia Casari; Brenda Romaldi; Lidia de Bari; Cinzia Antognelli; Tatiana Armeni (MDPI AG, 2023)
Hemoglobin is one of the proteins that are more susceptible to S-glutathionylation and the levels of its modified form, glutathionyl hemoglobin (HbSSG), increase in several human pathological conditions. The scope of the present review is to provide knowledge about how hemoglobin is subjected to S-glutathionylation and how this modification affects its functionality. The different diseases that showed increased levels of HbSSG and the methods used for its quantification in clinical investigations will be also outlined. Since there is a growing need for precise and reliable methods for markers of oxidative stress in human blood, this review highlights how HbSSG is emerging more and more as a good indicator of severe oxidative stress but also as a key pathogenic factor in several diseases.